‘Talking of China…’ : BBC radio talks on the People’s Republic of China 1949-1976 - Brayne Patterson, Mae (2020)
Unlike many of the studies of the geopolitical consequences of British radio, this project centres on the BBC’s Home Services as opposed to its External Services, focusing on the talks given by travellers to the People’s Republic of China. This project covers a period of significant changes in the geopolitical landscape of the Cold War, along with great changes in the relationship between Britain and China. Despite this, the main finding has been that the speakers were largely positive in their accounts. In both their remarks on China’s ancient civilisation and the modern changes implemented by the Communist Party, travellers were often complementary.